Analysis of Accounting Information Systems in Improving the Effectiveness of Drug Supplies (Case Study at the Puskesmas Kecamatan Waluran) - Ilham, Alipin; Sulaeman, Sulaeman; Noor, Iqbal (Universitas Dehasen Bengkulu, 2024)
The objectives of this study are: 1) To find out how the inventory accounting information system on medicines is effective at the Waluran Health Center, 2) To describe the effectiveness of the drug inventory at the Waluran Health Center, 3) To explain the obstacles faced in increasing the effectiveness of the drug inventory at the Waluran Health Center based on the Accounting Information System. The research uses qualitative methods with a descriptive approach, then data collection techniques using observation, interviews and documentation, and data analysis techniques using the Miles and Huberman model include: data collection, data reduction, data presentation and conclusions. The results of this study show: 1) The Drug Inventory Accounting Information System at the Waluran Health Center can be said to be running well, 2) The inventory of medicines at the Waluran Health Center has been effective, this is indicated by the realization of an accounting information system in its inventory, 3) significant obstacles in increasing the effectiveness of drug supplies at the Waluran Health Center, namely: 1) Human resource competence, 2) Monkey facilities, 3) Concurrent positions, 4) Lack of training.